Analysis of Product Quality Control Using the Taguchi Method and Principal Component Analysis (PCA) at the Pabrik Tahu Alami - Gulo, Trimodesman Hardinsyah; Sari, Devni Prima (Mathematical Journal of Modelling and Forecasting, 2024)
Indonesia's rapid economic growth in the global business sector has intensified competition among entrepreneurs, necessitating stringent control over product quality for companies to sustain their market position. This study utilizes the Taguchi method and Principal Component Analysis (PCA) to enhance quality control processes. The Taguchi method focuses on offline quality control with a single response, while PCA is employed for multiple responses. Experiments were conducted at Pabrik Tahu Alami, examining four factors: soybean rate, soaking time, boiling time, and whey water rate, each at three levels. The optimal combination determined was 3 kg of soybeans (level 1), 4 hours of soaking time (level 1), 20 minutes of boiling time (level 2), and 5 litres of whey water (level 2). These results provide a robust framework for optimizing product quality in similar production settings.